Nonincremental proper generalized decomposition solution of parametric uncoupled models defined in evolving domains. (14th September 2012) - Ammar, Amine; Cueto, Elías; Chinesta, Francisco
SUMMARY This work addresses the recurrent issue related to the existence of reduced bases related to the solution of parametric models defined in evolving domains. In this first part of the work, we address the case of decoupled kinematics, that is, models whose solution does not affect the domain in which they are defined. The chosen framework considers an updated Lagrangian description of the kinematics, solved by using natural neighbor Galerkin methods within a nonincremental space–time framework that can be generalized for addressing parametric models. Examples showing the performance and potentialities of the proposed methodology are included.Copyright © 2012 John Wiley & Sons, Ltd.